2011
DOI: 10.1111/j.1747-0285.2011.01211.x
|View full text |Cite
|
Sign up to set email alerts
|

1‐[(2‐Arylthiazol‐4‐yl)methyl]azoles as a New Class of Anticonvulsants: Design, Synthesis, In vivo Screening, and In silico Drug‐like Properties

Abstract: A series of novel thiazole incorporated (arylalkyl)azoles were synthesized and screened for their anticonvulsant properties using maximal electroshock and pentylenetetrazole models in mice. Among target compounds, 1-[(2-(4-chlorophenyl)thiazol-4-yl)methyl]-1H-imidazole (compound 4b), 1-[(2-phenylthiazol-4-yl)methyl]-1H-1,2,4-tria-zole (8a), and its 4-chlorophenyl analog (compound 8b) were able to display noticeable anticonvulsant activity in both pentylenetetrazole and maximal electroshock tests with percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…Commercial reagents such as selenium powder, pyrazole, n BuLi (1.6 M solution in hexane), NaBH 4 and 1,2‐dibromoethane were purchased from Sigma Aldrich and used without further purification. The starting materials were prepared according to literature methods: 4‐(chloromethyl)‐2‐phenylthiazole, 1‐(2‐bromoethyl)‐1 H ‐pyrazole, 4‐(2‐bromobenzyl)morpholine and N ‐(2‐bromobenzyl)‐ N ‐ethylethanamine . All the compounds were investigated in solution using multinuclear NMR spectroscopy ( 1 H, 13 C, 77 Se, 119 Sn where appropriate).…”
Section: Methodsmentioning
confidence: 99%
“…Commercial reagents such as selenium powder, pyrazole, n BuLi (1.6 M solution in hexane), NaBH 4 and 1,2‐dibromoethane were purchased from Sigma Aldrich and used without further purification. The starting materials were prepared according to literature methods: 4‐(chloromethyl)‐2‐phenylthiazole, 1‐(2‐bromoethyl)‐1 H ‐pyrazole, 4‐(2‐bromobenzyl)morpholine and N ‐(2‐bromobenzyl)‐ N ‐ethylethanamine . All the compounds were investigated in solution using multinuclear NMR spectroscopy ( 1 H, 13 C, 77 Se, 119 Sn where appropriate).…”
Section: Methodsmentioning
confidence: 99%
“…6) had the highest anticonvulsant activity. In particular, compound 19 showed 100% protection at the dose of 100 mg/kg against both PTZ-and MES-induced seizures [43]. mg/kg.…”
Section: N-(arylalkyl)triazolesmentioning
confidence: 96%
“…The last years of the research have confirmed that thiazole scaffold has diverse biological properties that can be used to treat many diseases, such as microbial infections (Bikobo et al 2017;Secci et al 2012;Łączkowski et al 2018a, 2018bZaki et al 2018;Ansari et al 2018), Parkinson's disease (Carradori et al 2018), cancer (de Santana et al 2018;Łączkowski et al 2014, 2016a, 2016bPiechowska et al 2019;Gomha et al 2018), epilepsy (Siddiqui and Ahsan 2010;Ahangar et al 2011;Łączkowski et al 2016a, 2016b, toxoplasmosis (Schultz et al 2014;Łączkowski et al 2018a, 2018b, and antioxidants (Geronikaki et al 2013;Djukic et al 2018). Considering the above-mentioned findings, we decided to design and synthesize the structure of hybrids incorporating both the thiazole ring and the cyclohexenyl moiety.…”
Section: Introductionmentioning
confidence: 98%